Optimization of novel pentablock copolymer based composite formulation for sustained delivery of peptide/protein in the treatment of ocular diseases. (17th February 2016) - Patel, Sulabh P.; Vaishya, Ravi; Patel, Ashaben; Agrahari, Vibhuti; Pal, Dhananjay; Mitra, Ashim k.
Abstract: This manuscript is focussed on the development of pentablock (PB) copolymer based sustained release formulation for the treatment of posterior segment ocular diseases. We have successfully synthesised biodegradable and biocompatible PB copolymers for the preparation of nanoparticles (NPs) and thermosensitive gel. Achieving high drug loading with hydrophilic biotherapeutics (peptides/proteins) is a challenging task. Moreover, small intravitreal injection volume (≤100 μL) requires high loading to develop a long term (six months) sustained release formulation. We have successfully investigated various formulation parameters to achieve maximum peptide/protein (octreotide, insulin, lysozyme, IgG-Fab, IgG, and catalase) loading in PB NPs. Improvement in drug loading can facilitate delivery of larger doses of therapeutic proteins via limited injection volume. A composite formulation comprised of NPs in gel system exhibited sustained release (without burst effect) of peptides and proteins, may serve as a platform technology for the treatment of posterior segment ocular diseases.